2021
DOI: 10.2174/1389202922666210219110831
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Protein Interaction Networks: Connectivity is Ruled by Gene Conservation, Essentiality and Function

Abstract: Background: Protein-protein interaction (PPI) networks are the backbone of all processes in living cells. In this work we relate conservation, essentiality and functional repertoire of a gene to the connectivity k (i.e. the number of interactions, links) of the corresponding protein in the PPI network. Methods: On a set of 42 bacterial genomes of different sizes, and with reasonably separated evolutionary trajectories, we investigate three issues: i) whether the distribution of connectivities changes betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The connectivity of proteins within a PPI network is another factor that can inform protein function as highly connected proteins are believed to perform essential biological functions and form a tightly connected core. In bacteria, these essential functions include processes related to translation, metabolism, transcription and replication [80].…”
Section: Guilt-by-associationmentioning
confidence: 99%
“…The connectivity of proteins within a PPI network is another factor that can inform protein function as highly connected proteins are believed to perform essential biological functions and form a tightly connected core. In bacteria, these essential functions include processes related to translation, metabolism, transcription and replication [80].…”
Section: Guilt-by-associationmentioning
confidence: 99%
“…In the meantime, intensive work continues to attempt to use the capabilities of modern computer tools for the analysis of available interactomes, especially bacterial ones. As illustrative examples, one can cite the studies of Wuchty et al [ 82 ] and Dilucca et al [ 83 ].…”
Section: Complete Interactomes—an (Unreachable?) Dream Of Systems Bio...mentioning
confidence: 99%
“…In the second study [ 83 ], the authors related the evolutionary conservation, essentiality, and functional repertoire of a gene to the connectivity k (the number of interprotein links) in the PPI network of 42 bacteria with genomes of different sizes, and reasonably separated evolutionary trajectories. In particular, they demonstrated that highly connected proteins (with connectivity a k ≥ 40) were encoded by genes that were conserved and essential among the species considered [ 84 ].…”
Section: Complete Interactomes—an (Unreachable?) Dream Of Systems Bio...mentioning
confidence: 99%